From molecular germanates to microporous Ge@C via twin polymerization. Issue 13 (2nd March 2016) - Kitschke, Philipp; Walter, Marc; Rüffer, Tobias; Lang, Heinrich; Kovalenko, Maksym V.; Mehring, Michael
Abstract : Porous Ge@C as anode material for Li-ion batteries was synthesized by the novel concept of twin polymerization starting from molecular germanates. Abstract : Four molecular germanates based on salicyl alcoholates, bis(dimethylammonium) tris[2-(oxidomethyl)phenolate(2-)]germanate (1 ), bis(dimethylammonium) tris[4-methyl-2-(oxidomethyl)phenolate(2-)]germanate (2 ), bis(dimethylammonium) tris[4-bromo-2-(oxidomethyl)phenolate(2-)]germanate (3 ) and dimethylammonium bis[2- tert -butyl-4-methyl-6-(oxidomethyl)phenolate(2-)][2- tert -butyl-4-methyl-6-(hydroxymethyl)phenolate(1-)]germanate (4 ), were synthesized and characterized including single crystal X-ray diffraction analysis. In the solid state, compounds1 and2 exhibit one-dimensional hydrogen bonded networks, whereas compound4 forms separate ion pairs, which are connected by hydrogen bonds between the dimethylammonium and the germanate moieties. The potential of these compounds for thermally induced twin polymerization (TP) was studied. Germanate1 was converted by TP to give a hybrid material (HM-1 ) composed of phenolic resin and germanium dioxide. Subsequent reduction with hydrogen provided a microporous composite containing crystalline germanium and carbon (Ge@C –C-1, germanium content ∼20%). Studies onC-1 as an anode material for Li-ion batteries revealed reversible capacities of ∼370 mA h gGe@C −1 at a current density up to 1384 mA g −1 without apparent fading for 500 cycles.